A feasibility and safety study of computed tomography-guided percutaneous microwave ablation: a novel therapy for multiple synchronous ground-glass opacities of the lung. (1st January 2020) - Huang, Guanghui; Yang, Xia; Li, Wenhong; Wang, Jiao; Han, Xiaoying; Wei, Zhigang; Meng, Min; Ni, Yang; Zou, Zhigeng; Wen, Qiang; Dai, Jianjian; Zhang, Tiehong; et al.
Abstract: Purpose: The present study retrospectively evaluated the feasibility, safety, and short-term efficacy of computed tomography (CT)-guided percutaneous microwave ablation (MWA) to treat multiple synchronous ground-glass opacities (GGOs) of the lung. Materials and Methods: From October 2016 to May 2019, 33 patients (9 males and 24 females, mean age: 59.6 ± 10.0 years) with multiple GGOs (103 GGOs with mean size 12.3 ± 6.3 mm) were enrolled in this study. Patients underwent 66 procedures of CT-guided percutaneous MWA. The feasibility, safety, local progression-free survival, and overall survival were evaluated. Results: The technical success and technique efficacy rate were 100% and no MWA procedure-related deaths were reported. The median follow-up period was 18.1 (range: 6.8–37.7) months. Major complications included pneumothorax (11/66, 16.7%), pleural effusion (2/66, 3.0%), pneumonia (3/66, 4.5%), and nerve injury (1/66, 1.5%), which were well controlled by appropriate treatment. Minor complications included pneumothorax (38/66, 57.6%), pleural effusion (43/66, 65.2%), hemoptysis (13/66, 19.7%), subcutaneous emphysema (4/66, 6.1%), and hemothorax (2/66, 3.0%). Currently, all patients are alive without local progression or tumor recurrence, despite the relatively insufficient follow-up time. Conclusion: CT-guided percutaneous MWA for the treatment of multiple synchronous lung GGOs is feasible, safe, and efficacious over short-term follow-up. It may also be employed as an alternative approach for nonsurgical candidates. A longer follow-up is warranted to evaluate the oncologic outcomes.